Strategi Komunikasi Pemasaran Integrated Marketing Communication (IMC) Pose In Hotel Dalam Meningkatkan Jumlah Pengunjung - Aziz, Agusto Faizal; Hindra H, Nurnawati; Widiyowati, Estu (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
This study aims to study the integrated marketing communication strategy carried out by PoseIn Hotel to increase the number of visitors. Marketing communication is an important factor inthe tight competition in the hotel industry. Implementation of an effective communicationstrategy can increase the competitiveness of hotels in the midst of increasingly competitivebusiness competition due to globalization. This study uses a descriptive type of research with aqualitative approach, namely by describing how the integrated marketing communicationstrategy or IMC carried out by Pose In Hotel in increasing visitors. The researcher obtained datafrom interviews, observations and documentation. The results of the study showed that Pose InHotel had taken marketing steps in accordance with the integrated marketing communicationstrategy or IMC explained by the researcher, namely: (1) Pose In Hotel carried out promotionsusing IMC marketing communication elements. Planning was also carried out carefully in orderto carry out balanced promotions to the target audience (2) implementing 8 IMC elements,namely advertising, direct marketing, sales promotion, personal selling, word of mouthmarketing, interactive marketing, public relations. The IMC strategy has been proven to be ableto increase visitors to come to stay at Pose In Hotel. Meanwhile, after planning andimplementation, evaluation is also considered an important benchmark to determine the extent towhich the promotion is carried out to increase the number of visitors.Keywords: Pose In Hotel, Integrated Marketing Communication.